Open a world of possible real stories about the joy and power of reading - Robinson, Richard; Bridges, Lois (New York Scholastic, 2014)
"188 distinct voices from every region of the country, including Alaska and Hawaii ... all celebrate reading for enriching their lives ..., and share a fervent wish that children around the world enjoy abundant access to books so that they too may 'live many parallel lives' and dream what may be possible for their own."
Keywords: Books and reading